Pemberdayaan Pamsimas dengan Digitilisasi sistem berbasis website dan Arduino - Achmad Vandian Nur; Fenilinas Adi Artanto; Khusna Santika Rahmasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The increasing speed of information accessibility marked by the birth of digital technology has changed the way we live our daily lives. Skills in this technological field can help us overcome various challenges in the digital era. Of the many skills in the field of technology and information today, the ability and mastery of the Internet of Things (IoT) is one of the most important areas. One key aspect of being able to understand Internet of Things technology is its utilization for communities in need. This Community Service Activity is in the form of community empowerment with the theme